Kontribusi Hasil Tambak Udang Windu Terhadap Tingkat Kesejahteraan Rumah Tangga Petani Tambak di Kelurahan Lakkang Kecamatan Tallo Kota Makassar - Syahruddin, Syahruddin (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to : (1) find out how much the contribution of tiger shrimp ponds to the household income of pond farmers in Lakkang Sub-District, Tallo District, Makassar City; (2) To determine the level of welfare of the households of tiger shrimp farms in Lakkang Village, Tallo District, Makassar City. This research is a qualitative descriptive study. Data sources used were farmers in Lakkang Sub-District, Tallo District, Makassar City, which totaled 43 people. The sampling technique in this study used the random sampling method. Data collection is done using a questionnaire. The data analysis technique used is qualitative descriptive analysis. The results showed that: (1) the contribution of ponds obtained by pond farmers in Lakkang Sub-District, Tallo District, Makassar City was 85%. (2) The welfare level of Lakkang Village farmers' farms is as follows: (a) The welfare level of farmers stage 1 as many as 3 respondents with a percentage of 7%, the welfare level of farmers belonging to the stage 2 prosperity as many as 19 respondents with a percentage of 44%, the welfare level of farmers classified as stage 3 as many as 14 respondents with a percentage of 33%. prosperity stage 3 plus as many as 7 respondents with a percentage of 16%; (c) the contribution of farm results to the level of income between 41-50 percent places two households in the stage II prosperous family, the contribution of the results of the farm to the income level between 51 - 60 percent placing 2 households in the stage II prosperous family and 1 household in the family stage III prosperity, the contribution of farm results to income levels between 61 - 70 percent places 1 household in stage II prosperous families and 1 household in stage III prosperous families, the contribution of farm results to income levels between 71 - 80 percent placing 1 household in stage I prosperous families, 3 households in stage II prosperous families, 4 households in stage III prosperous families, and 2 households in stage III plus prosperous families. the contribution of farm results to income levels between 81-90 percent places 2 households in the first stage prosperous family, 4 households in the stage III stage of prosperous family, and 2 households in the stage III prosperous family stage plus. the contribution of farm results to income levels between 91 - 100 percent places 11 households in stage II prosperous families, 3 households in stage III prosperous families, and 3 households in stage III plus prosperous families.